ACCESSIBILITY OF FIRST-LEVEL HEALTH SERVICES IN PARIGI SUB-VILLAGE, LEBBOTENGNGAE VILLAGE, CENRANA DISTRICT, MAROS REGENCY - Surahmawati Surahmawati (Universitas Islam Negeri Alauddin Makassar, 2021)
Background: The level of equalization of health services has not been achieved optimally, there are still about 36.8% of Indonesians living in rural areas are very difficult to access first-rate health services. While in South Sulawesi itself there are still about 32% of the population who are very difficult to access health services.Objective: The purpose of this study is to see an overview of the accessibility of first-level health services (Puskesmas) in Parigi Hamlet, Lebbotengngae village, Maros Regency, South Sulawesi.Method: This research is a descriptive survey conducted in December 2020 with a total of 91 samples taken from the number of households in Parigi hamlet, sampling is done by total sampling techniques. Data collection using questionnaires analyzed usingunivariate analysis and presented in the form of frequency distribution tables.Result: It found that the accessibility of health services geographically is unaffordable, whereas accessibility is economically affordableSuggestion: Local government should pay attention to the availability and smoothness of transportation so that people can easily access health services